2002
DOI: 10.2535/ofaj.79.113
|View full text |Cite
|
Sign up to set email alerts
|

SEM Study on the Dorsal Lingual Surface of the Large Flying Fox, Pteropus vampyrus.

Abstract: The dorsal lingual surface of the large flying foxes were examined by scanning electron microscopy. Filiform, fungiform and vallate papillae were observed. The filiform papillae were distributed over the entire dorsal surface of the tongue. The filiform papillae notably differed in morphology by their location on the tongue and could be classified into 6 types: 1) scale-like, 2) giant trifid, 3) small crown-like, 4) large crown-like, 5) long conical and 6) short conical papillae. The fungiform papillae were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
32
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 20 publications
15
32
0
Order By: Relevance
“…This confirmed in the previous articles that, the filiform papillae have many divisions, such as they were classified as seven subtype in; bat by (Park & Hall, 1951), while our study in Egyptian fruit bat and (Kobayashi & Shimamura, 1982;Emura et al, 2002b;Abumandour & El-Bakary, 2013) describe six subtypes of the filiform papillae. Five subtypes were noted in; lesser dog-faced fruit and nectarivorous bats (Emura et al, 2001b;Greenbaum & Phillips;Emura et al, 2012;Masuko et al) and in cat (Ojima et al, 1997).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This confirmed in the previous articles that, the filiform papillae have many divisions, such as they were classified as seven subtype in; bat by (Park & Hall, 1951), while our study in Egyptian fruit bat and (Kobayashi & Shimamura, 1982;Emura et al, 2002b;Abumandour & El-Bakary, 2013) describe six subtypes of the filiform papillae. Five subtypes were noted in; lesser dog-faced fruit and nectarivorous bats (Emura et al, 2001b;Greenbaum & Phillips;Emura et al, 2012;Masuko et al) and in cat (Ojima et al, 1997).…”
Section: Discussionsupporting
confidence: 91%
“…As in the previous published data, the lingual papillae were species-specific, in which differing in their number among mammalian species, these differences may depend on dissimilarities in diet, feeding habits and handling of food in mouth (Emura et al, 2002b;Abumandour & El-Bakary), the previous data clear in; our study in Egyptian fruit bat, this confirmed by presence of four types of lingual papillae; two mechanical and two gustatory as noted in; bats (Selim et al, 2008;Abumandour & El-Bakary;Abayomi et al, 2009), moreover other mammals have four lingual papillae; as in our study in New Zealand white rabbits; one mechanical (filiform) and three gustatory (fungiform, foliate and circumvallate) as noted in; rats (Nasr et al, 2012), bank vole (Jackowiak & Godynicki, 2005), dog and fox (Emura et al, 2006). However, three types of lingual papillae; one mechanical (filiform) and two gustatory (fungiform and circumvallate) as noted in; bats (Pastor et al, 1993;Emura et al, 2001b;Park & Lee, 2009;Masuko et al, 2007), however, there were two types only of papillae (filiform and fungiform) in hematophagous bats (Masuko et al).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Therefore, the lingual papillae of the eastern grey kangaroo are generally similar to those of the red kangaroo. Three vallate papillae were also found on the tongues of marsupials (Kubota et (Kubota, 1966), insectivores (Chunhabundit et al, 1992) and Chiroptera (Emura et al, 2001;Emura et al, 2002b). In this study, the eastern grey kangaroo showed a triangular arrangement of the three vallate papillae, with the apex of the triangle directed posteriorly.…”
Section: Discussionsupporting
confidence: 59%